The Influence of The Work Environment and Employee Engagement on Employee Retention - Andari Andari; Nafiudin Nafiudin; Ratih Purnamasari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Companies develop and progress influenced by human resources. The company's ability to retain employees is the main thing that must be considered. Employee retention is affected by several variables including work environment and employee engagement. This study aims to determine the effect of the work environment and employee engagement on employee retention at CV. Symphony of Eternal Prosperity. This type of research is quantitative using a research sample of 83 employees. The data were obtained using questionnaires and interviews and processed using the SPSS version 22 statistical program. Based on the results of the study, it can be concluded that the work environment affects employee retention, employee engagement affects employee retention, and the work environment and employee engagement simultaneously affect employee retention CV. Symphony of Eternal Prosperity.